MAIN FACTORS OF FORMING MODERN CULTURAL IMAGE OF YOUTH - Karimova Dilfuza Abdukayumova (Galaxy International Interdisciplinary Research Journal, 2021)
Today, on the one hand, the youth of our country is determined by the fact that their life coincides with the globalization, rapid information, modernization processes, and the ongoing radical reforms, on the other, on the principles of socio-economic, political, legal and democratic development. This, in turn, leads us to believe in the youth movement, the position and responsibility of the state and society in the implementation of the prospects of building a democratic, free and prosperous homeland, free and prosperous life.